1967
DOI: 10.1111/j.1399-3054.1967.tb07217.x
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and Genetic Control of Dormancy in Picea abies

Abstract: The effects of temperature, photoperiod and chilling on the leafing‐out of Norway spruce, Picea abies (L.) Karst. were studied. High temperature promotes breakage of post‐dormancy, long photoperiods having no such effect. Photoperiod and chilling cause the breakage of true dormancy. However, under field conditions, photoperiod will have no effect on leafing‐out date in the spring. By use of clonal material it was possible to show substantial genetic differences between individuals in response to temperature an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
1

Year Published

1974
1974
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 9 publications
3
39
1
Order By: Relevance
“…However, Hibbard & Elkinton (2015) did not fi nd any such differences between introduced O. brumata populations on Vancouver Island and in Massachusetts in North America. The pattern recorded might be an adaptation to match larval eclosion with bud burst of host trees, a critical synchrony for many spring folivores (Visser & Holleman, 2001;van Asch & Visser, 2007), with trees from high-latitude populations frequently requiring a lower temperature sum for fl ushing in spring than their southern conspecifi cs (Worrall & Mergen, 1967;Myking & Heide, 1995). Southern moth species spreading northwards would be subject to the risk of a mismatch between budburst and egg hatching in spring unless they can adapt to hatch at a lower temperature sum (Tikkanen et al, 2006;Saikkonen et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, Hibbard & Elkinton (2015) did not fi nd any such differences between introduced O. brumata populations on Vancouver Island and in Massachusetts in North America. The pattern recorded might be an adaptation to match larval eclosion with bud burst of host trees, a critical synchrony for many spring folivores (Visser & Holleman, 2001;van Asch & Visser, 2007), with trees from high-latitude populations frequently requiring a lower temperature sum for fl ushing in spring than their southern conspecifi cs (Worrall & Mergen, 1967;Myking & Heide, 1995). Southern moth species spreading northwards would be subject to the risk of a mismatch between budburst and egg hatching in spring unless they can adapt to hatch at a lower temperature sum (Tikkanen et al, 2006;Saikkonen et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Long days compensate partially for a lack of chilling during rest break in Pinus sylvestris L. (Jensen andGatherum 1965, Hoffman andLyr 1967), Picea abies (L.) Karst. (Nienstaedt 1967, Worrall andMergen 1967) and several other tree species (Nienstaedt 1966, Farmer 1968, Campbell and Sugano 1975, Hinesley 1982, Garber 1983. Some results indicate that there is a critical photoperiod for bud burst in beech (Fagus sylvatica L.) seedlings, even when they are fully chilled (Heide 1993a).…”
Section: Introductionmentioning
confidence: 97%
“…After transplanting, the seedlings and cuttings were moved outdoors and exposed to natural chilling and freezing temperatures until December 5, 1997. On this date the material was presumed to be fully chilled (Worrall and Mergen 1967, Sarvas 1974, Hänninen 1990). The pots were isolated from each other with sand.…”
Section: Chilling Conditionsmentioning
confidence: 99%
“…The temperatures in March and October -the period at the beginning and end of bud formation -had a significant impact on annual needle production (r = 0.36, a = 0.05, figure 9). Worral and Mergen [33] report on the control of bud break by temperature. Gruber [11] describes the parallel development of the shoot and its buds and found that the final needle primordia can be initiated in October.…”
Section: Response Function Analysismentioning
confidence: 99%